Gemini surfactant: A novel flotation collector for harvesting of microalgae by froth flotation. (March 2019) - Huang, Zhiqiang; Cheng, Chen; Liu, Zuwen; Luo, Wuhui; Zhong, Hong; He, Guichun; Liang, Changli; Li, Liqing; Deng, Lanqing; Fu, Weng
Graphical abstract: Gemini surfactant as a collector for froth flotation harvesting of microalgae. Highlights: A novel Gemini surfactant BCBD was introduced in microalgae flotation harvesting. BCBD exhibited excellent collecting power for Chlorella vulgaris. BCBD displayed superior flotation performances than conventional surfactant CTAB. Gemini is a promising collector for froth flotation harvesting of microalgae. Abstract: Froth flotation has been proved to be a promising approach for commercial scale harvesting of microalgae. However, all the surfactants used in the microalgae flotation harvesting process are conventional monomeric surfactants contain a single similar hydrophobic group in the molecule, which results in a low harvesting efficiency. In this work, a novel Gemini surfactant, N, N′-bis(cetyldimethyl)-1, 4-butane diammonium dibromide (BCBD) was prepared, and originally recommended as a collector for froth flotation harvesting of Chlorella vulgaris from culture medium. The performance of BCBD was compared with the results acquired using its conventional monomeric surfactant cetyl trimethyl ammonium bromide (CTAB). The bench-scale flotation results showed that BCBD had excellent collecting power for Chlorella vulgaris. Achieving the obviously superior flotation harvesting performance (flotation recovery increased by 21.4% and enrichment ratio increased by 22.9), the dosage of Gemini type BCBD collector is five times less than that of monomeric CTAB collector.